THE EXISTENCE OF AN AUTONOMOUS DEPARTMENT OF CSR (CORPORATE SOCIAL RESPONSIBILITY) AND ITS IMPACT ON MANAGER’S PERCEPTIONS ABOUT CSR - Pouliopoulos, Leonidas; Geitona, Mary; Pouliopoulos, Theofilos; Triantafillidou, Amalia (Journal of European Economy, 2017)
This study examines whether a separate – autonomous or not – CSR department within the company, affects the opinions of managers of Greek enter prises about practices and activities of CSR. The findings suggest that managers of companies operating in Greece, without a special CSR department, accept a greater degree of institutionalization of CSR, since it offers financial and tax advantages in contrast to the companies with a specialized department. In other, we found that the way a company manages its activities and practices of CSR is not largely affect the perceptions of managers or directors, in connection to whether a company has a separate CSR department, or not.